Strengthening the institutional structure of urban development land market in Malaysia - Omar, Ismail; Othman, Asiah; Wardata, Djurjani; Djojomarton, Prijono Nugroho (Faculty of Geoinformation Science And Engineering, 2007)
There will be no development without land being available in the market. Although land is available in the market for development, without landowners’ willingness to participate or transfer their land to land developers under development arrangement, there will be no development takes place too. This is known as land supply constraints that restrict the flow of land supply onto the land market for development purposes. In other word, land supply constraints disturb the effectiveness of the land market. As a result, the underutilized area may become derelict and needs regeneration as part of urban renewal programs. The study begins with discussion on institutional economics analysis and transaction costs approach. In particular, review on literature concentrates on the elements of land supply constraints with the purpose to feed the empirical analysis in the case study areas. In doing so, the study on the institutional structure of the land supply in the market may disclose ways to improve the land supply constraints for land development. Empirically, the study seeks to investigate sources of land supply constraints in the case study area of MAS Kampong Baru, Kuala Lumpur. Data were gathered using interviews with landowners of undeveloped and developed sites to examine why they had paid effort to develop or simply abandoned their lands undeveloped. Analysis had been undertaken by qualitative techniques on respondents using coding, either direct or indirect quotations. Landowners respondent were taken randomly to represent predetermined zones within the case study areas. Property professional respondents were taken purposively for interviews. Data analysed were presented in the forms of charts, histograms, diagrams and illustrations to ease discussion. One of the main findings is that landowners were unwilling to undertake redevelopment due to land supply constraints as revealed by transaction cost embedded within their status of landownership, attitudes, physical, planning, valuation and market constraints. In the end, the findings enable various interested parties to realize their roles and responsibilities in their future direction to redevelop Kampong Baru in Kuala Lumpur. One of the ways is to undertake joint effort in applying land readjustment technique to redevelop Kampong Baru.